2022
DOI: 10.1155/2022/1645265
|View full text |Cite
|
Sign up to set email alerts
|

Moroccan Medicinal Plants Used to Treat Cancer: Ethnomedicinal Study and Insights into Pharmacological Evidence

Abstract: Cancer is one of the major medical challenges, with an unacceptably high death toll worldwide. In Morocco, medicinal plants continue to play a pivotal therapeutic role despite the development of modern sanitation systems. In the current study, an ethnobotanical survey was carried out at the Moroccan national institute of oncology, Rabat, and we aimed at (1) establishing an exhaustive inventory of indigenous knowledge of Moroccan medicinal plants used to manage cancer and (2) confirming the reported ethnopharma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 86 publications
3
11
0
Order By: Relevance
“…E. alata is one of the medicinal plants used to treat cancer in Morocco 14 , 66 and in other countries, such as Algeria and Palestine (East Jerusalem) 89 , 90 . Methanolic or ethanolic extracts made from the plant have revealed marked inhibitory effects on the proliferation of breast cancer cell lines in vitro .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…E. alata is one of the medicinal plants used to treat cancer in Morocco 14 , 66 and in other countries, such as Algeria and Palestine (East Jerusalem) 89 , 90 . Methanolic or ethanolic extracts made from the plant have revealed marked inhibitory effects on the proliferation of breast cancer cell lines in vitro .…”
Section: Resultsmentioning
confidence: 99%
“…Toxic plants found in northeastern Morocco have been inventoried as well [20]. Other studies cover different local areas or they are concerned with specific pathology or disorders, such as the Moroccan plants used to treat cancers [14,66], skin affections [67], kidney diseases [68], or cardiovascular diseases [69]. Some Moroccan plants have been largely studied, such as the endemic argan [Argania spinosa (L.) Skeels], which is well known for its famous oil extracted from argan seeds [70].…”
Section: Ephedra Species Found In Morocco and Their Medicinal Usesmentioning
confidence: 99%
“…It covers about 4.500 species spanning 940 genera and 135 plant families, with the Rif and Atlas mountains are the crucial zones for endemic species (Chaachouay et al 2022). The recording of indigenous knowledge through ethnobotanical studies holds paramount importance for the conservation and effective utilization of biological resources (El Hachlafi et al, 2022). Establishing the local names and indigenous uses of plants carries substantial societal benefits .…”
Section: Introductionmentioning
confidence: 99%
“…In this context, we selected three medicinal plants to test the single and combined antibacterial efect of their EOs on pathogenic strains. Tese plants were chosen based on our previous ethnobotanical surveys which have demonstrated their therapeutic and culinary virtues [11][12][13][14]. In addition, some in vitro studies have revealed their signifcant antimicrobial abilities [8,15,16].…”
Section: Introductionmentioning
confidence: 99%